The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/wrr.12516
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of injured skin and peripheral nerves requires control of wound contraction, not scar formation

Abstract: We review the mounting evidence that regeneration is induced in wounds in skin and peripheral nerves by a simple modification of the wound healing process. Here, the process of induced regeneration is compared to the other two well-known processes by which wounds close, i.e., contraction and scar formation. Direct evidence supports the hypothesis that the mechanical force of contraction (planar in skin wounds, circumferential in nerve wounds) is the driver guiding the orientation of assemblies of myofibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 62 publications
2
67
0
1
Order By: Relevance
“…Wound healing involves the processes of regeneration, contraction, and scar formation. The force of contraction orients the myofibroblasts and collagen fibers, which contribute to scar formation . Full thickness wounds retain at most 80% of their function and strength at closure.…”
Section: Discussionmentioning
confidence: 99%
“…Wound healing involves the processes of regeneration, contraction, and scar formation. The force of contraction orients the myofibroblasts and collagen fibers, which contribute to scar formation . Full thickness wounds retain at most 80% of their function and strength at closure.…”
Section: Discussionmentioning
confidence: 99%
“…After severe trauma, in the adult mammal occurs a wound constriction and scar formation. An appropriate control of wound contraction can induce the regeneration of wounded skin [20]. More specifically it has been observed that the regeneration of the highest quality is induced under wound conditions the contraction was inhibited [21].…”
Section: Short Commentarymentioning
confidence: 99%
“…It has been suggested that appropriate disruption of this barrier by a scaffold could enhance injury repair processes . For example, porous collagen scaffolds can induce regeneration in skin wounds in a manner that correlates with a decrease in the rate of wound contraction, similar to regeneration induced in peripheral nerves . In addition, mechanical force transmission and mechanosensing of cells within tissues generate changes in the shape of the injured tissue, such as size modification, and tissue patterning, by modulating various cell functions .…”
Section: Introductionmentioning
confidence: 99%